Estratégias de gestão local para o monitoramento da cobertura vacinal infantil - Silva, Cristiane Moraes da (2024)
Vaccination coverage for children under 1 year of age falls short of the 95% target, exposing the population to the risk of reintroducing vaccine-preventable diseases. The objective was to analyze local management strategies for monitoring vaccination coverage in children under 1 year of age. The study is linked to the research line "Vulnerabilities of the population in the context of rurality" of the Graduate Program in Health and Rurality at the Federal University of Santa Maria (PPGSR/UFSM). It is a single, integrated, explanatory case study with a qualitative approach, using data triangulation and thematic content analysis. Fourteen health professionals, either working as vaccinators or in management roles related to immunization, were interviewed. Municipal Health Plans and vaccination coverage indicators from the Vaccination Panel and the Previne Brasil Program formed the document analysis. Direct observation of the organizational and structural aspects of vaccination rooms was also conducted. The study was carried out in Health Region 20, Rota da Produção, in Rio Grande do Sul. This region is characterized by the presence of small municipalities where the majority of healthcare services are provided by Primary Care. Additionally, the region has a large rural and indigenous population. For the selection of the research participants, municipalities were divided into two groups according to the results of Indicator 5 – Proportion of one-year-old children vaccinated in Primary Care against diphtheria, tetanus, pertussis, hepatitis B, infections caused by Haemophilus influenzae type B, and inactivated poliomyelitis – from the Previne Brasil Program, for the second quarter of 2023. Based on the indicator classification, one group included municipalities with indicator results below 67%, and the other with results equal to or greater than 67% for the period. Subsequently, 5 municipalities were randomly selected from each group.The results showed that the organization of vaccination services has distinct characteristics regarding schedules, availability of vaccines, and identification and active outreach for those missing vaccinations. Local management of vaccination coverage is incipient, with no routine monitoring of indicators and the establishment of targets below the ideal level. Organizational, geographic, and sociocultural barriers were identified as obstacles to achieving adequate vaccination coverage. In geographic terms, the barriers are related to the distance between vaccination rooms and the rural population, access via unpaved roads, and limited access to the internet and phone signal in some areas. The presence and work of community health agents, management support, and community ties were listed as potential strengths. It is concluded that there is no routine analysis of vaccination coverage indicators, and they are not used for planning and monitoring vaccination activities. Organizational barriers hinder access to vaccination, making it necessary to rethink the management of primary healthcare territories based on local needs.